(3eHGOF GdeMGSHI GdeGdjI (B:s (3GdOhQ GdeMGSHjI heTGcd GdGYJQGa hGdbjGS hGdGaUGM (B/s - (3eWQ, eMeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2007)
(3deMI Yf GdeMGSHI hfTCJgG,GdEjWGQ GdeaGgjej Gh GdfXQj ddeMGSHI,fXGe GdbjO GdeROhL heYGOdI GdejRGfjI,GdOhQI GdeMGSHjI ddYedjGJ GdeGdjI,GdJShjGJ GdLQOjI,GdeMGSHI Yf GdGjQGOGJ hGdeUQhaGJ,GdeMGSHI Yf GdeJOGhdI Gh bUjQI GdGLd,GdeMGSHI Yf GdGSJKeGQGJ WhjdI GdCLd,GdeMGSHI Yf GdCUhd WhjdI GdCLd,GdeMGSHI Yf GdeWdhHGJ,GdbhGFe GdeGdjI GdNJGejIs
Keywords: (3GdeGdjI GdYGeIs; (3GdeMGSHIs; (3GdeMGSHI(B- (3GdeGdjI GdYGeIs